Harnessing coaches' expertise: creating 11 sport-specific profiles for talent orientation - Johanna Ochs; Andreas Hohmann; Johan Pion; Johan Pion (Frontiers in Sports and Active Living)
IntroductionIn Germany, there is no systematic approach to talent orientation that recommends an appropriate sport for children. Talent detection is the first step of the talent process, in which children's motor profiles are assessed using standardized test batteries. In the second step, talent orientation, these profiles are weighted with sport profiles to derive sport recommendations for each child. But how are these sport profiles built? The aim of this study is to engage coaches in the creation of sport profiles.MethodsGerman coaches (n = 256) of gymnastics, handball, judo, soccer, swimming, table tennis, tennis, track & field participated in a survey using the German Motor Test 6–18 plus ball throwing and agility test. Eight sports were included. Judo was divided into light and heavy weight categories, and track & field into endurance running, sprinting/jumping, and throwing, resulting in eleven disciplines. Each discipline had a separate standardized questionnaire, with judo categories combined into one.ResultsThe results show individual profiles of relevant characteristics for each sport discipline. ANOVA and z-transformed means revealed different ratings of the test items, enabling the development of specific combinations of the most important test items for each discipline. The validity of these sport discipline-specific profiles was tested using discriminant analyses, which assigned coaches to their respective sport discipline. A linear discriminant analysis correctly classified 78.1% of coaches to their respective sport discipline. When comparing one sport discipline to all others, correct classification ranged from 82.2% to 92.7%.DiscussionBased on the coaches' ratings, eleven different sport discipline profiles were developed, each with its own combination of key test items. Track & field sprinting/jumping was most clearly distinguished from other disciplines. Overlaps were found in the profiles of handball and tennis, as well as judo and swimming. These findings help coaches utilize the profiles for talent orientation.